Continuous‐Flow Synthesis of CdSe Quantum Dots: A Size‐Tunable and Scalable Approach. Issue 35 (15th July 2013) - Mirhosseini Moghaddam, Mojtaba; Baghbanzadeh, Mostafa; Sadeghpour, Amin; Glatter, Otto; Kappe, C. Oliver
Abstract In recent years, continuous‐flow/microreactor processing for the preparation of colloidal nanocrystals has received considerable attention. The intrinsic advantages of microfluidic reactors have opened new opportunities for the size‐controlled synthesis of nanocrystals either in the laboratory or on a large scale. Herein, an experimentally simple protocol for the size‐tunable continuous‐flow synthesis of rather monodisperse CdSe quantum dots (QDs) is presented. CdSe QDs are manufactured by using cadmium oleate as cadmium source, selenium dioxide as selenium precursor, and 1‐octadecene as solvent. Exploiting selenium dioxide as selenium source and 1‐octadecene as solvent allows execution of the complete process in open air without any requirement for air‐free manipulations using a glove box or Schlenk line. Continuous‐flow processing is performed with a stainless steel coil of 1.0 mm inner diameter pumping the combined precursor solution through the reactor by applying a standard HPLC pump. The effect of different reaction parameters, such as temperature, residence time, and flow rate, on the properties of the resulting CdSe QDs was investigated. A temperature increase from 240 to 260 °C or an extension of the residence time from 2 to 20 min affords larger nanocrystals (range 3–6 nm) whereas the size distribution does not change significantly. Longer reaction times and higher temperatures result in QDs with lower quantum yields (range 11–28 %). The quality of the synthesized CdSe QDs was confirmed by UV/Vis and photoluminescence spectroscopy, small‐angle X‐ray scattering, and high‐resolution transmission electron microscopy. Finally, the potential of this protocol for large‐scale manufacturing was evaluated and by operating the continuous‐flow process for 87 min it was possible to produce 167 mg of CdSe QDs (with a mean diameter of 4 nm) with a quantum yield of 28 %.